Cell type diversification and phenotype convergence underlying white fin-ornamentation of cyprinid fishes - Delai Huang; Tiffany Liu; August A. Carr; Pietro H. de Mello; Yipeng Liang; Leah P. Shriver; François Chauvigné; Stephen L. Johnson; Joan Cerdà; Gary J. Patti; David M. Parichy (Proceedings of the National Academy of Sciences, 2026)
Neural crest–derived cells offer valuable opportunities to dissect mechanisms of cell fate specification and differentiation and the underpinnings of cell type diversification over evolutionary time. Particularly useful for such analyses are pigment cells of ectothermic vertebrates that arise from neural crest cells or via latent neural crest–derived stem cells. Among these are white cells, leucophores, present in a variety of species that contribute to patterns on the body or ornamentation on the fins. To better understand developmental and evolutionary origins of these cells, we examined leucophores harboring deposits of yellow/orange carotenoids—xantholeucophores—of zebrafish and leucophores of white cloud minnow. We show that white phenotypes of both cell types require sepiapterin reductase and an accumulation of pale and colorless pteridines. We further demonstrate that xantholeucophores of zebrafish develop from yellow, sepiapterin-rich xanthophore-like cells and that this transition requires both gap junctional communication and the aquaglyceroporin/peroxiporin channel Aquaporin 3, revealing similarities and differences in differentiation and patterning compared to pigment cells on the body. These findings identify xantholeucophores of zebrafish and leucophores of white cloud minnow as distinct developmentally, genetically, and biochemically from other white cells of zebrafish—melanoleucophores—that develop directly from melanophores and depend on guanine crystals, as well as white cells of medaka fish and anemonefish. Our results highlight remarkable convergences and parallelisms in the acquisition of white cell phenotypes within and between phylogenetic lineages and identify this as a rich system for enquiries into the evolutionary individuation of novel cell types.